Synthesis and physicochemical properties of sulfonated poly(aryl ether) PEMs containing phthalazinone and oxadiazole moieties. (April 2018) - Jin, Cuihong; Zhu, Xiuling
In this work, 2, 5-bis(4-fluorophenyl)-1, 3, 4-oxadiazole (2F-Oz) is synthesized and successfully polymerized with 4-(4-hydroxyaryl)-phthalazin-1-one (DHPZ) through polycondensation to produce poly(ether 1, 3, 4-oxidiazole) containing phthalazinone units (PPEO) with intrinsic viscosity 1.54 dL g −1 . A series of sulfonated poly(ether-1, 3, 4-oxidiazole)s (SPPEOs) with different degrees of sulfonation are prepared via postsulfonation reaction. The chemical structure of PPEO and SPPEOs was characterized through FT-IR and proton nuclear magnetic resonance, respectively. SPPEOs have excellent film-forming properties and readily dissolve in polar aprotic solvents, such as dimethyl sulfoxide, N-methyl-2-pyrrolidone (NMP), and so on. The water uptake of these SPPEO membranes with measured ion-exchange capacity of 1.13–1.61 mmol g −1 was 15.7–34.1% at 25°C and 17.9–59.8% at 60°C, and swelling ratio was 5.9–14.2% at 25°C and 6.6–18.1% at 60°C, respectively. The proton conductivity of SPPEO-1.61 is 0.045 S cm −1 at 30°C and 0.065 S cm −1 at 80°C, and the tensile strength of the SPPEO-1.61 is 48 MPa, and its elongation at break was 21%. The thermal and chemical stability of the SPPEOs is also examined.